The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1134/s000629791510020x
|View full text |Cite
|
Sign up to set email alerts
|

Level of blood cell-free circulating mitochondrial DNA as a novel biomarker of acute myocardial ischemia

Abstract: Changes in the level of blood cell-free circulating mitochondrial DNA were examined during experimental adrenaline-induced myocardial injury in rats. The amount of mitochondrial DNA in the blood was significantly elevated at 48 and 72 h after subcutaneous injection of adrenaline solution, and it was accompanied by development of multiple small-focal myocardial ischemia. This suggests that the measured level of blood cell-free circulating mitochondrial DNA might be used as a biomarker of acute myocardial ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…It was already explored the dynamics of the level of free circulating blood plasma mtDNA in acute myocardial ischemia and observed the increase in blood plasma mtDNA concentration [57]. Recently, we found the raise of concentration of free circulating mitochondrial DNA in blood after injection of adrenaline that caused the development of multiple small focal myocardial ischemia in Wistar rats [8, 9]. Recent observations [10] reveal the molecular mechanism behind the development of acute heart failure in animal models, where mitochondrial DNA is an important pathogenic factor.…”
Section: Introductionmentioning
confidence: 99%
“…It was already explored the dynamics of the level of free circulating blood plasma mtDNA in acute myocardial ischemia and observed the increase in blood plasma mtDNA concentration [57]. Recently, we found the raise of concentration of free circulating mitochondrial DNA in blood after injection of adrenaline that caused the development of multiple small focal myocardial ischemia in Wistar rats [8, 9]. Recent observations [10] reveal the molecular mechanism behind the development of acute heart failure in animal models, where mitochondrial DNA is an important pathogenic factor.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of circulating cell-free mitochondrial DNA (ccf-mtDNA) in 2000 [1], prompted a wave of studies assessing the utility of ccf-mtDNA as a biomarker of disease [2][3][4][5][6][7], detection of cancers [8][9][10][11][12] and susceptibility to comorbidities during HIV infection [13,14].…”
mentioning
confidence: 99%
“…Mitochondrial DNA activates p38 mitogen-activated protein kinase (MAPK) by TLR9 with leakage of matrix metalloproteinase 8 and 9 in neutrophils [36]. Later, another study observed the increase of MMP9 and phosphorylated p38 in response to mitochondrial DNA treatment of neutrophils [37]. In addition, Wei et al [30] also noted similar observation: pretreatment with ODN2088 (a TLR9 inhibitor) prevented p38 MAPK pathway activation and MMP8 leakage.…”
Section: Mitochondrial Dna and Toll-like Receptormentioning
confidence: 80%